Apathy and Color-Blindness in Privatized Immigration Control. Issue 4 (October 2020) - Ebert, Kim; Liao, Wenjie; Estrada, Emily P.
Despite several widely covered scandals involving the role of for-profit corporations in administering immigration policy, the privatization of immigration control continues apace with the criminalization of immigration. How does this practice sustain its legitimacy among the public amid so much controversy? Recent studies on the criminalization of immigration suggest that supporters would explicitly vilify immigrants to defend the privatization of immigration control. Research on racialized social control, on the other hand, implies that proponents would avoid explicit racism and vilification and instead rely on subtler narratives to validate the practice. Drawing on a qualitative analysis of over 600 frames derived from nearly 200 news media articles spanning over 20 years, we find that journalists and their sources rarely vilify immigrants to justify the privatization of immigration control. Instead, they frame the privatization of immigration detention as a normal component of population management and an integral part of the U.S. economy through what we call the apathy strategy —a pattern of void in which not only the systematic oppression of immigrants is underplayed, immigrant themselves also become invisible.